Origin and temporal variability of unusually low δ13C-DOC values in two High Arctic catchments - Hindshaw, Ruth; Lang, S; Bernasconi, S; Heaton, T; Lindsay, M; Boyd, E (Journal of Geophysical Research: Biogeosciences, 2016)
The stable carbon isotopic composition of dissolved organic matter (δ13C-DOC) reveals information about its source and extent of biological processing. Here we report the lowest δ13C-DOC values (−43.8‰) measured to date in surface waters. The streams were located in the High Arctic, a region currently experiencing rapid changes in climate and carbon cycling. Based on the widespread occurrence of methane cycling in permafrost regions and the detection of the pmoA gene, a proxy for aerobic methanotrophs we conclude that the low δ13C-DOC values are due to organic matter partially derived from methanotrophs consuming biologically produced, 13C-depleted methane. These findings demonstrate the significant impact that biological activity has on the stream water chemistry exported from permafrost and glaciated environments in the Arctic. Given that the catchments studied here are representative of larger areas of the Arctic, occurrences of low δ13C-DOC values may be more widespread than previously recognized, with implications for understanding C cycling in these environments. Peer reviewed